Analisis Kinerja Keuangan Laporan Realisasi Pendapatan dan Belanja Daerah Kota Tasikmalaya Tahun 2020-2022 - Salsabila, Malika; Siboro, Sonny Fransisco; Damayanti, Novita; Kamilah, Shafa Tasya (ISAS, 2024)
Although Tasikmalaya City’s revenue has increased in recent years, this study shows that the city government is still dependent on support from the central government. Nonetheless, the evaluation shows that the local financial management of Tasikmalaya City is working well and efficiently, although there are some problems with the management of routine expenditures that need to be improved. The results suggest that the Tasikmalaya municipal government should improve the management of routine expenditure to be more in line with the regional revenue and expenditure budget (APBD) and to optimize the use of capital to improve the effectiveness and efficiency of government operations. This could improve local financial independence and reduce their dependence on the central government. This research is quantitative and uses data from the annual report on the realization of the Tasikmalaya city regional revenue and expenditure budget from 2020 to 2022. The analysis was conducted using ratio analysis techniques to evaluate the efficiency, effectiveness, growth, and harmony of regional financial management. Furthermore, research can be conducted to identify methods that can be used by the Tasikmalaya city government to improve the management of routine expenditure as well as to find components that cause a decrease in revenue in 2022. In addition, further research could concentrate on how improvements in routine expenditure management impact local economic growth and the quality of public services. Keywords: financial performance, realization, regional, tasikmalaya.